Different expression strategy: multiple intronic gene clusters of Box H/ACA snoRNA in Drosophila melanogaster. - Huang, Z.P.; Zhou, H.; Liang, D.; Qu, L.H. (Journal of Molecular Biology, 2004)
The high degree of rRNA pseudouridylation in Drosophila melanogaster provides a good model for studying the genomic organization, structural and functional diversity of box H/ACA small nucleolar RNAs (snoRNAs). Accounting for both conserved sequence motifs and secondary structures, we have developed a computer-assisted method for box H/ACA snoRNA searching. Ten snoRNA clusters containing 42 box H/ACA snoRNAs were identified from D.melanogaster. Strikingly, they are located in the introns of eight protein-coding genes. In contrast to the mode of one snoRNA per intron so far observed in all animals, our results demonstrate for the first time a novel polycistronic organization that implies a different expression strategy for a box H/ACA snoRNA gene when compared to box C/D snoRNAs in D.melanogaster. Mutiple isoforms of the box H/ACA snoRNAs, from which most clusters are made up, were observed in D.melanogaster. The degree of sequence similarity between the isoforms varies from 99% to 70%, implying duplication events in different periods and a trend of enlarging the intronic snoRNA clusters. The variation in the functional elements of the isoforms could lead to partial alternation of snoRNA's function in loss or gain of rRNA complementary sequences and probably contributes to the great diversity of rRNA pseudouridylation in D.melanogaster.